Over and under the rainforest - Messner, Kate (Messner, Kate. Over and under., 2020)
"Under the canopy of the rainforest, hundreds of animals make their homes--from the slender parrot snake to the colorful poison dart frog. But up in the trees hides a whole other world, where toucans and pale-billed woodpeckers chatter and call, capuchin monkeys swing from the vines, and sleek-furred jaguars rule the night. In this exuberant book, discover the wonder and activity that lie hidden among the roots, above the winding rivers...and under the brilliant green trees of the rainforest."--